Jihad and Social Transformation at the Al-Faqih 2 Cibiru Islamic Boarding School - Virginisa, Nabila (STAI AL-FALAH CICALENGKA, 2023)
Jihad for Muslims is an effort to realize the will of Allah SWT. expressed through his religion. Apart from jihad by fighting on the battlefield, there is jihad which is more important than fighting on the battlefield without having to draw a sword or raise a weapon, as is the case at the Al-Faqih 2 Islamic boarding school in fighting jihad by combining Islamic religious education with social activism, encouraging its students. to get involved in efforts to improve the lives of the people around them. This research aims to explain the concept of jihad in Islam as applied by the Al-Faqih 2 Cibiru Islamic boarding school, identify the positive impact of jihad on social transformation in the community around the Al-Faqih 2 Cibiru Islamic boarding school and identify challenges and efforts in social transformation in the surrounding community. al-faqih Islamic boarding school 2 Cibiru. This research focuses on how the concept of jihad in Islam is applied by the al-faqih 2 Cibiru Islamic boarding school, what the positive impact of jihad is on social transformation in the community around the al-faqih 2 Cibiru Islamic boarding school and what the challenges and efforts are in social transformation in the surrounding community. al-faqih Islamic boarding school 2 Cibiru. Research findings show that the Al-Faqih 2 Cibiru Islamic boarding school in Bandung City has students who are mostly UIN Bandung students who come from various regions. Ustadz Syihabudiin, who is the head of the Al-Faqih 2 Cibiru Islamic boarding school, Bandung City, together with the students collaborate with each other to convey da'wah or teach knowledge about Islam directly to the surrounding community which indirectly has had a positive impact on social transformation in both the social field. as well as religion for the surrounding community, although there are challenges that the Al-Faqih 2 Islamic boarding school must face, this does not dampen the enthusiasm for fighting for the surrounding community in the form of preaching. Keywords: Jihad, Social Impact, Social Transformation. Abstrak Jihad bagi umat Islam adalah salah satu usaha untuk merealisasikan kehendak Allah swt. yang diekspresikan melalui agamanya. Selain jihad dengan bertempur di medan perang ada jihad yang lebih utama dari berperang di medan tempur tanpa harus menghunus pedang dan mengangkat senjata seperti halnya yang terjadi di pondok pesantren Al-Faqih 2 dalam berjihad dengan cara menggabungkan pendidikan agama Islam dengan aktivisme sosial, mendorong para santrinya untuk terlibat dalam upaya meningkatkan kehidupan masyarakat di sekitar mereka. Penelitian ini bertujuan untuk menjelaskan konsep jihad dalam Islam yang di aplikasikan oleh pondok pesantren al-faqih 2 Cibiru, mengidentifikasi dampak positif dari jihad terhadap transformasi sosial di masyarakat sekitar pondok pesantren al-faqih 2 Cibiru serta mengidentifikasi tantangan dan upaya dalam transformasi sosial di masyarakat sekitar pondok pesantren al-faqih 2 Cibiru. Penelitian ini berfokus pada bagaimana konsep jihad dalam Islam yang di aplikasikan oleh pondok pesantren al-faqih 2 Cibiru, bagaimana dampak positif dari jihad terhadap transformasi sosial di masyarakat sekitar pondok pesantren al- faqih 2 Cibiru serta bagaimana tantangan dan upaya dalam transformasi sosial di masyarakat sekitar pondok pesantren al-faqih 2 Cibiru. Temuan penelitian menunjukkan bahwa pondok pesantren Al-Faqih 2 Cibiru Kota Bandung yang memiliki santri mayoritas mahasiswa UIN Bandung yang berasal dari berbagai daerah. Ustadz Syihabudiin yang merupakan pimpinan pondok pesantren Al- Faqih 2 Cibiru Kota Bandung bersama para santri saling berkolaborasi untuk yang menyampaikan dakwah atau mengajarkan ilmu – ilmu tentang Islam secara langsung kepada masyarakat di sekitarnya yang secara tidak langsung telah memberikan dampak positif bagi trasnformasi sosial baik bidang sosial maupun agama bagi masyarakat di sekitarnya, meskipun ada tantangan yang harus dihadapi oleh pondok pesantren Al-Faqih 2, namun hal tersebut tidak menyurutkan semangat untuk berjihad kepada masyarakat sekitar dalam bentuk dakwahnya. Kata kunci: Jihad, Dampak Sosial, Transformasi sosial.